Islamic Banking Regulation and Supervision : Survey Results and Challenges - Song, In.; Oosthuizen, Carel (Washington, D.C. : International Monetary Fund, 2014)
The growing presence of Islamic banking needs to be accompanied by the development of effective regulation and supervision. This paper examines the results of the survey conducted by the International Monetary Fund to document international experiences and country practices related to legal and prudential frameworks governing Islamic banking activities. Although a number of countries have made considerable progress in creating legal, regulatory, and supervisory frameworks that accommodate Islamic banking, there are substantial differences. This paper also identifies a number of challenges faced by regulatory and supervisory agencies regarding Islamic banking.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet